SUSTAINABLE BALLAST WATER MANAGEMENT: MITIGATING ECOLOGICAL IMPACTS AND SUPPORTING MARINE AND COASTAL BIODIVERSITY - Silvia Gabrina Tonyes; Yan Ramona; Yaya Rukayadi; Yenni Ciawi (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS• Reviews global ballast water management for ecological sustainability• Integrates technological, policy, and social perspectives• Links ballast water control to Sustainable Development Goals (SDGs)• Identifies hybrid treatment systems as most effective and eco-safe• Proposes strategies for harmonized global compliance and cooperationABSTRACTBallast water is crucial for the stability and safety of ships but poses significant environmental, economic, and public health risks due to the introduction of invasive species, pathogens, and pollutants into marine ecosystems. This review explores the ecological impacts of ballast water discharge, including biodiversity loss, ecosystem disruption, and public health threats from pathogens and harmful algal blooms. Economic consequences, such as damage to fisheries, aquaculture, and coastal infrastructure, are discussed, along with the social impacts on communities reliant on marine resources. Existing regulatory frameworks, such as the International Maritime Organization's Ballast Water Management Convention, and national policies aim to mitigate these challenges but face implementation and enforcement hurdles. Advancements in treatment technologies are reviewed, including mechanical, chemical, physical, and emerging methods like advanced oxidation processes, electrochlorination, and nanotechnology. Integrated treatment systems are highlighted for their potential to address the limitations of single-method approaches. Case studies illustrate successful implementations, while challenges in cost, scalability, and compliance are identified. The review emphasizes the alignment of ballast water management practices with sustainable development goals, advocating for innovation, international collaboration, and capacity building to enhance effectiveness. Future directions include the optimization of treatment technologies, harmonization of regulations, and incentivization of compliance to achieve global environmental and economic resilience. This review underscores the urgency of advancing sustainable ballast water management to protect marine ecosystems, support coastal economies, and promote public health worldwide.